Cover crop root morphology rather than quality controls the fate of root and rhizodeposition C into distinct soil C pools - Engedal, Tine; Magid, Jakob; Hansen, Veronika; Rasmussen, Jim; Sørensen, Helle; Stoumann Jensen, Lars (Global change biology, 2023)
Cover crops increase carbon (C) inputs to agricultural soils, and thus have the potential to mitigate climate change through enhanced soil organic carbon (SOC) storage. However, few studies have explored the fate of belowground C inputs associated with varying root traits into the distinct SOC pools of mineral‐associated organic carbon (MAOC) particulate organic carbon (POC). Therefore, a packed 0.5 m column trial was established with 0.25 m topsoil and 0.25 m subsoil with four cover crops species (winter rye, oilseed radish, chicory, and hairy vetch) known to differ in C:N ratio and root morphology. Cover crops were 14 CO 2 ‐labeled for 3 months, and then, half of the columns were sampled to quantify root and rhizodeposition C. In the remaining columns, plant shoots were harvested and the undisturbed soil and roots were left for incubation. Bulk soil from both sampling times was subjected to a simple fractionation scheme, where 14 C in the <50 and >50 μm fraction was assumed to represent MAOC and POC, respectively. The fast‐growing rye and radish produced the highest root C. The percentage loss of C via rhizodeposition (%ClvR) showed a distinct pattern, with 22% for the more branched roots (rye and vetch) and 6%–8% for the less branched roots (radish and chicory). This suggests that root morphology plays a key role in determining rhizodeposition C. After 1 year of incubation at room temperature, the remaining MAOC and POC were positively correlated with belowground inputs in absolute terms. However, topsoil MAOC formation efficiencies (cover crop‐derived MAOC remaining as a share of belowground inputs) were higher for vetch and rye (21% and 15%, respectively) than for chicory and radish (9% and 10%, respectively), suggesting a greater importance of rhizodeposition (or indirectly, root morphology) than solely substrate C:N ratio for longer term C stabilization.